Injectable silk fibroin sustained-release gel and preparation method thereof

CN122998466APending Publication Date: 2026-10-30ZHEJIANG LAIYIMEI BIOPHARMACEUTICAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611228270.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-13
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0008]本申请的主要目的在于提供一种可注射型丝素蛋白缓释凝胶及其制备方法,旨在解决现有技术存在的凝胶化时间不可精确控制、制备工艺复杂、成本高昂以及缺乏对环境刺激的响应能力的技术问题

Benefits of technology

(1)凝胶化时间精确可控:本申请制备的预凝胶溶液在注射后3min-8min内完成凝胶化,既保证了充分的操作时间,又避免了过长的凝胶化等待时间,满足不同临床应用的需求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122998466A_ABST
    Figure CN122998466A_ABST
Patent Text Reader

Abstract

The application discloses an injectable silk fibroin sustained-release gel and a preparation method thereof. The sustained-release gel is composed of aldehyde-hyaluronic acid, amino-silk fibroin and poly(N-isopropylacrylamide-co-acrylic acid), and an interpenetrating network structure is formed through sequential self-assembly of Schiff base reaction and temperature-sensitive phase transition. The oxidation degree of the aldehyde-hyaluronic acid is 15%-30%, and the molecular weight is 100kDa-300kDa. The amino substitution degree of the amino-silk fibroin is 20%-40%, and the concentration is 4%-12% w / v. The molar fraction of acrylic acid of the poly(N-isopropylacrylamide-co-acrylic acid) is 5%-20%, the molecular weight is 10kDa-30kDa, and the concentration is 2%-6% w / v. The gel has pH / temperature dual response characteristics, the gelation time is accurately controllable, and the compression modulus can reach 50kPa-150kPa. The gel preparation process is relatively simple, and the biocompatibility is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of biomedical materials technology, and in particular to an injectable silk fibroin sustained-release gel and its preparation method. Background Technology

[0002] Silk fibroin, a natural high-molecular-weight structural protein, has been widely used in drug delivery systems, tissue engineering scaffolds, and medical devices due to its excellent biocompatibility, biodegradability, and good mechanical properties. Derived from silkworm silk, silk fibroin is a pure natural protein obtained from silkworm cocoons after degumming. It possesses good biodegradability, low immunogenicity, and excellent mechanical properties, making it an ideal biomedical material.

[0003] Currently, injectable silk fibroin gel technology mainly employs the following two preparation methods: First, in-situ gel is formed by blending polyethylene glycol or propylene glycol with silk fibroin solution; second, injectable hydrogel is prepared by double cross-linking hyaluronic acid with silk fibroin.

[0004] On the one hand, existing silk fibroin-polyethylene glycol in-situ gelation technology involves mixing a 3% to 30% (by weight) aqueous solution of silk fibroin with a 50% to 100% (by weight) solution of polyethylene glycol or propylene glycol at a volume ratio of 2:1 to 1:2. The mixture solidifies within 1 to 10 minutes to form an injectable gel. While this technology has a simple preparation process, it suffers from the problem of inaccurate control over the gelation time. The solidification time fluctuates significantly within the range of 1 to 10 minutes, making it difficult to meet the precise gelation time requirements of different clinical scenarios.

[0005] On the other hand, the hyaluronic acid / silk fibroin dual crosslinking technology involves aldehyde-modifying hyaluronic acid, grafting it with dopamine, mixing it with a silk fibroin solution, and adding a soluble iron salt to form a dual crosslinked network structure. While this technology improves mechanical properties, its preparation process is complex, requiring pre-aldehyde-modification of hyaluronic acid, grafting with dopamine, and finally forming coordination bonds with iron salts. The entire process is cumbersome and costly. Furthermore, the chemical crosslinking agents (such as iron salts) used in this system may adversely affect bioactive drugs, limiting its application in the delivery of biopharmaceuticals.

[0006] More critically, existing technologies generally lack the ability to respond to environmental stimuli. For example, when gels are applied to the tumor microenvironment, they cannot intelligently respond to release based on the specific acidic environment of the tumor site (pH 6.5-6.8) or temperature changes at the site of inflammation, resulting in simplistic drug release kinetics and difficulty in achieving precise treatment. Furthermore, existing gels are prone to needle blockage during injection, and their integration with surrounding tissues after injection is poor, affecting treatment efficacy.

[0007] Therefore, developing an injectable silk fibroin sustained-release gel with controllable gelation time, excellent mechanical properties, environmental responsiveness, and good biocompatibility has become an urgent technical problem to be solved in this field. Summary of the Invention

[0008] The main objective of this application is to provide an injectable silk fibroin sustained-release gel and its preparation method, aiming to solve the technical problems of existing technologies, such as the inability to precisely control the gelation time, complex preparation process, high cost, and lack of responsiveness to environmental stimuli.

[0009] To achieve the above objectives, this application provides an injectable silk fibroin sustained-release gel, composed of the following components: Aldehyaluronic acid with an oxidation degree of 15%-30% and a molecular weight of 100kDa-300kDa; Aminated silk fibroin, with an amino substitution degree of 20%-40% and a concentration of 4%-12% w / v; Poly(N-isopropylacrylamide-co-acrylic acid), with an acrylic acid molar fraction of 5%-20%, a molecular weight of 10kDa-30kDa, and a concentration of 2%-6% w / v; The volume ratio of the aldehyde-modified hyaluronic acid, amino-modified silk fibroin, and poly(N-isopropylacrylamide-co-acrylic acid) is 1:(0.8-1.2):(0.3-0.7). The injectable silk fibroin sustained-release gel forms an interpenetrating network structure through sequential self-assembly of Schiff base reaction and thermosensitive phase transition, exhibiting dual pH / temperature response characteristics.

[0010] Optionally, the aldehyde-modified hyaluronic acid has an oxidation degree of 20%-25% and a molecular weight of 150kDa-200kDa; The amino-substituted silk fibroin has an amino substitution degree of 25%-35% and a concentration of 6%-10% w / v; The poly(N-isopropylacrylamide-co-acrylic acid) has an acrylic acid molar fraction of 10%-15%, a molecular weight of 15kDa-25kDa, and a concentration of 3%-5% w / v.

[0011] Optionally, the gelation time of the injectable silk fibroin sustained-release gel is 3 min-8 min, and the compression modulus is 50 kPa-150 kPa.

[0012] Optionally, it may also include a pharmaceutically active ingredient selected from one or more of chemotherapeutic drugs, protein drugs, growth factors, or anti-inflammatory drugs.

[0013] Optionally, the chemotherapy drug is doxorubicin, and the drug loading is 1%-3% of the total weight of the gel; The protein drug is epidermal growth factor, with a loading of 50 μg / mL-200 μg / mL; The anti-inflammatory drug is dexamethasone, with a loading of 0.3%-0.8% w / v.

[0014] Optionally, the drug release rate of the injectable silk fibroin sustained-release gel at pH 6.5 is 2 to 3 times that at pH 7.4.

[0015] Optionally, the injectable silk fibroin sustained-release gel exhibits a drug release rate that is more than 50% higher at 40°C compared to that at 37°C.

[0016] Furthermore, to achieve the above objectives, this application also provides a method for preparing the above-mentioned injectable silk fibroin sustained-release gel, comprising the following steps: Hyaluronic acid was dissolved in deionized water to prepare a 1%-3% w / v solution. Sodium periodate was added to carry out an oxidation reaction for 20-28 hours. Ethylene glycol was added to terminate the reaction. After dialysis with deionized water and freeze drying, aldehyde-modified hyaluronic acid was obtained. Silkworm cocoons are boiled in a 0.3%-0.7% w / v sodium carbonate solution to degumme them, resulting in pure silk fibroin fibers. The pure silk fibroin fibers are dissolved in a lithium bromide solution, and after stirring and dialysis, pure silk fibroin protein is obtained. The pure silk fibroin protein is then aminated, dialyzed, and freeze-dried to obtain aminated silk fibroin protein. N-Isopropylacrylamide and acrylic acid were dissolved in deionized water at a molar ratio of (80-90):(10-20), with a total monomer concentration of 8%-12% w / v. Ammonium persulfate was added as an initiator, and the reaction was carried out under nitrogen protection for 5-7 hours. The product was purified by dialysis and then freeze-dried to obtain poly(N-isopropylacrylamide-co-acrylic acid). The aldehyde-modified hyaluronic acid, the amino-modified silk fibroin, and the poly(N-isopropylacrylamide-co-acrylic acid) were dissolved in phosphate buffer solution with a pH of 7.2-7.6 and mixed at a volume ratio of 1:(0.8-1.2):(0.3-0.7) to obtain the injectable silk fibroin sustained-release gel.

[0017] Optionally, the molar ratio of sodium periodate to hyaluronic acid glucose unit is 0.25-0.35:1; The pure silk fibroin was modified by amination with ethylene glycol diglycidyl ether, wherein the molar ratio of ethylene glycol diglycidyl ether to the pure silk fibroin was (1.5-2.5):1. The amount of ammonium persulfate added is 0.5%-1.5% of the total weight of the monomers.

[0018] Optionally, before obtaining the injectable silk fibroin sustained-release gel, the method further includes: pre-dissolving the active pharmaceutical ingredient in the corresponding buffer solution and then mixing it with the solutions of each component.

[0019] Compared with the prior art, this application has the following beneficial effects: (1) Precise and controllable gelation time: The pre-gel solution prepared in this application completes gelation within 3-8 minutes after injection, which ensures sufficient operation time and avoids excessively long gelation waiting time, thus meeting the needs of different clinical applications.

[0020] (2) Significantly improved mechanical properties: Through the design of interpenetrating network structure, the compressive modulus of the composite gel in this application can reach 50-150 kPa, which is much higher than the 10-30 kPa of single component gel, and can withstand mechanical stress under physiological conditions without structural damage.

[0021] (3) Dual environmental response characteristics: The gel of this application has dual pH / temperature response capabilities. In an acidic environment of pH 6.5, the drug release rate of the gel is 2-3 times that under pH 7.4 conditions; at an inflammatory temperature of 40℃, the drug release rate is more than 50% higher than that at 37℃, achieving precise drug delivery. Attached Figure Description

[0022] Figure 1 This is a schematic diagram of the structure of the injectable silk fibroin sustained-release gel in the embodiments of this application; Figure 2 This is a flowchart illustrating the preparation process of the injectable silk fibroin sustained-release gel in this application embodiment. Detailed Implementation

[0023] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of the embodiments. Based on the embodiments of this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.

[0024] This application provides an injectable silk fibroin sustained-release gel, composed of the following components: Aldehyaluronic acid with an oxidation degree of 15%-30% and a molecular weight of 100kDa-300kDa.

[0025] Aminated silk fibroin with an amino substitution degree of 20%-40% and a concentration of 4%-12% w / v.

[0026] Poly(N-isopropylacrylamide-co-acrylic acid), with an acrylic acid molar fraction of 5%-20%, a molecular weight of 10kDa-30kDa, and a concentration of 2%-6% w / v.

[0027] The volume ratio of aldehyde-modified hyaluronic acid, amino-modified silk fibroin, and poly(N-isopropylacrylamide-co-acrylic acid) is 1:(0.8-1.2):(0.3-0.7).

[0028] The injectable silk fibroin sustained-release gel provided in this application forms an interpenetrating network structure through sequential self-assembly of Schiff base reaction and thermosensitive phase transition, exhibiting dual pH / temperature response characteristics.

[0029] Specifically, the injectable silk fibroin sustained-release gel provided by this application includes: methylated hyaluronic acid (oxidation degree 15%-30%, molecular weight 100-300kDa), aminoated silk fibroin (amino substitution degree 20%-40%, concentration 4%-12% w / v), and poly(N-isopropylacrylamide-co-acrylic acid) (acrylic acid molar fraction 5%-20%, molecular weight 10-30kDa, concentration 2%-6% w / v). The above parameter range can ensure that the reactivity of the polymer chain segments is moderate, so that there will be no insufficient cross-linking and gel formation failure due to too low oxidation degree / substitution, and no excessive solution viscosity due to too high parameters, resulting in loss of injectable fluidity.

[0030] This application specifies that the volume mixing ratio of the above three components is 1:(0.8-1.2):(0.3-0.7), which ensures that the two crosslinking mechanisms can be adapted simultaneously. At the same time, this application clarifies that the molding method is sequential self-assembly: first, Schiff base chemical crosslinking occurs between aldehyde and amino groups, and then temperature phase change is achieved by relying on thermosensitive copolymers, finally forming an interpenetrating network. This product has the ability to release drugs in both pH and temperature responses.

[0031] In other embodiments, the degree of oxidation of aldehyde-modified hyaluronic acid is 20%-25%, and the molecular weight is 150kDa-200kDa; the degree of amino substitution of amino-modified silk fibroin is 25%-35%, and the concentration is 6%-10% w / v; the acrylic acid molar fraction of poly(N-isopropylacrylamide-co-acrylic acid) is 10%-15%, the molecular weight is 15kDa-25kDa, and the concentration is 3%-5% w / v.

[0032] Specifically, this embodiment further narrows down the key indicators of each raw material to the optimal range, precisely locking in the optimal formula suitable for the human physiological environment: aldehyde-modified hyaluronic acid is optimized to an oxidation degree of 20%-25% and a molecular weight of 150kDa-200kDa. Within this range, the Schiff base crosslinking rate is stable, avoiding problems such as needle blockage due to excessively fast crosslinking or gel collapse due to excessively slow crosslinking; amino-modified silk fibroin is optimized to an amino substitution degree of 25%-35% and a concentration of 6%-10% w / v, ensuring sufficient grafting sites for silk fibroin while maintaining good solution fluidity; the thermosensitive copolymer is optimized to an acrylic acid molar fraction of 10%-15%, a molecular weight of 15kDa-25kDa, and a concentration of 3%-5% w / v. The acrylic acid groups are responsible for sensing pH changes, and this ratio allows the thermosensitive and pH response performance to reach a balance.

[0033] In other embodiments, the gelation time of the injectable silk fibroin sustained-release gel is 3 min-8 min, and the compression modulus is 50 kPa-150 kPa.

[0034] This embodiment limits the gelation time to 3-8 minutes. The mixed precursor solution can remain liquid to meet the injection requirements of the syringe. After injection into the body, it solidifies rapidly within 3-8 minutes to avoid the diffusion of liquid raw materials in the body and the inability to form a fixed shape. At the same time, the compressive modulus is limited to 50kPa-150kPa. This mechanical strength matches the mechanical environment of human subcutaneous soft tissue and lesion sites. If the modulus is too low, the gel is prone to breakage and disintegration. If the modulus is too high, the gel texture is too hard, and it will produce obvious foreign body sensation when implanted into the body. Through the above limitations, the finished gel can meet the mechanical and operational time requirements for clinical implantation.

[0035] In other embodiments, a pharmaceutically active ingredient is also included, which is selected from one or more chemotherapeutic drugs, protein drugs, growth factors, or anti-inflammatory drugs.

[0036] This embodiment clarifies that the gel can carry four specific types of drugs: chemotherapy drugs, protein drugs, growth factors, and anti-inflammatory drugs. Utilizing an interpenetrating network porous structure, the gel can physically encapsulate these drugs, while the network structure also prevents rapid drug diffusion, achieving a sustained-release effect. These four types of drugs correspond to four major clinical scenarios: tumor treatment, wound repair, tissue regeneration, and local anti-inflammatory treatment, thus clarifying the specific drug carrier application direction of this gel and enhancing the product's actual medical functional characteristics.

[0037] In other embodiments, the chemotherapeutic drug may be doxorubicin, with a drug loading of 1%-3% of the total weight of the gel; the protein drug may be epidermal growth factor, with a loading of 50 μg / mL-200 μg / mL; and the anti-inflammatory drug may be dexamethasone, with a loading of 0.3%-0.8% w / v.

[0038] This embodiment further specifies the specific types and precise drug loading parameters of three typical drugs to avoid the defects of drug loading imbalance: 1. The chemotherapy drug doxorubicin is selected, with a drug loading of 1%-3%. A drug loading of less than 1% cannot achieve an effective anti-tumor concentration, while a loading of more than 3% will produce significant cytotoxicity; 2. The protein drug epidermal growth factor is selected, with a loading controlled at 50μg / mL-200μg / mL, which can avoid spatial conformational denaturation and loss of biological activity caused by excessive protein drug loading; 3. The anti-inflammatory drug dexamethasone is selected, with a concentration of 0.3%-0.8% w / v. This concentration can effectively inhibit local inflammation without hormone side effects.

[0039] In other embodiments, the drug release rate of the injectable silk fibroin sustained-release gel at pH 6.5 is 2 to 3 times that at pH 7.4.

[0040] This embodiment quantifies the specific pH-responsive drug release performance of the gel, using the actual pH environment in the human body as a constraint: setting the pH of normal body tissues at 7.4 and the pH of the inflammatory / tumor microenvironment at 6.5, it clarifies that the drug release rate under acidic conditions is 2-3 times that under neutral conditions. This performance originates from the protonation / deprotonation changes of acrylate groups in the gel segments: under acidic conditions, acrylate groups protonate, the gel network pores expand, and drug release accelerates; under neutral physiological conditions, the network contracts, and drug release is slow. This specific ratio characteristic demonstrates that the gel can recognize the acidic microenvironment of lesions, achieving targeted drug release to the lesion and reducing drug exposure in normal tissues.

[0041] In other embodiments, the injectable silk fibroin sustained-release gel showed a drug release rate that was more than 50% higher at 40°C than at 37°C.

[0042] This embodiment builds upon the pH response performance and supplements it with specific quantitative indicators for temperature response, corresponding to differences in human body temperature: using the normal human body temperature of 37°C and the local fever temperature of the lesion of 40°C as test conditions, the drug release rate at 40°C is limited to be more than 50% higher than at 37°C. This performance is achieved through the N-isopropylacrylamide temperature-sensitive unit in the formulation. When the temperature exceeds the minimum critical dissolution temperature, the polymer chain segments change from hydrophilic to hydrophobic, the gel network shrinks rapidly, and the internal drug release is accelerated. This embodiment, combined with the above pH response data, fully clarifies the specific quantitative performance parameters of the gel's dual response.

[0043] The sequential self-assembly process of the injectable sustained-release gel, including room-temperature pre-crosslinking and in vivo thermosensitive phase transition, provided in this application is broken down step by step as follows: 1. Room temperature liquid precursor stage (pre-injection): After mixing the three polymer solutions of aldehyde-modified hyaluronic acid, amino-modified silk fibroin, and thermosensitive copolymer, the mixture maintains a low viscosity liquid state at room temperature, exhibiting good fluidity and meeting the requirements for clinical syringe injection. At this stage, only a slow Schiff base pre-reaction occurs, preventing rapid solidification and needle clogging, perfectly adapting to injectable requirements, corresponding to the controllable gelation time of 33 min-8 min as claimed in the claim.

[0044] 2. Step 1: Schiff base chemical cross-linking (preliminary network formation at room temperature): The aldehyde groups of aldehyde-modified hyaluronic acid undergo a covalent Schiff base reaction with the amino groups on the surface of amino-modified silk fibroin, initially constructing the first layer of rigid chemical cross-linked network. This covalent network structure is stable, providing basic mechanical support for the gel, ensuring that the gel does not easily collapse after molding, and matching the mechanical properties of a compressive modulus of 50kPa-150kPa.

[0045] 3. Second Step: Thermosensitive Physical Phase Transition (Secondary In vivo network formation): After the gel is injected into the human body at 37°C, the thermosensitive polymer (N-isopropylacrylamide-co-acrylic acid) within the system rapidly undergoes a thermosensitive phase transition, changing from a hydrophilic, expansive state to a hydrophobic, contractile state, forming a second layer of physical cross-linked network. The two networks intertwine and entangle, ultimately forming a complete interpenetrating network structure, such as... Figure 1 As shown.

[0046] 4. Dual-response drug release mechanism: Acrylic groups in the network endow the gel with pH responsiveness, allowing the network to expand and accelerate drug release in an acidic environment; NIPAM segments endow the network with temperature responsiveness, allowing the network to contract and accelerate drug release in a high-temperature environment.

[0047] This application provides a method for preparing the above-mentioned injectable silk fibroin sustained-release gel, comprising the following steps: S1. Dissolve hyaluronic acid in deionized water to prepare a 1%-3% w / v solution, add sodium periodate to carry out an oxidation reaction for 20-28 hours, add ethylene glycol to terminate the reaction, and obtain aldehyde-modified hyaluronic acid by dialyzing with deionized water and freeze drying.

[0048] This step uses a 1%-3% w / v hyaluronic acid aqueous solution as the reaction substrate. This concentration range ensures sufficient dispersion of hyaluronic acid molecules, avoiding molecular aggregation and uneven oxidation reactions due to excessive concentration, while insufficient production efficiency due to excessively low concentration. Sodium periodate is used as a specific oxidant to directionally break the vicinal diol structure on the hyaluronic acid molecular chain to generate aldehyde groups. A reaction time of 20-28 hours is set to ensure the oxidation reaction proceeds fully. After the reaction, ethylene glycol is added to quench residual sodium periodate, terminating excessive oxidation and preventing a significant decrease in molecular weight due to excessive chain breakage of hyaluronic acid. Subsequent dialysis removes small molecule byproducts and unreacted reagents, and freeze-drying yields a solid powder for precise subsequent solution preparation. The final product's aldehyde group content matches the requirements of the Schiff base crosslinking reaction.

[0049] S2. Boil silkworm cocoons in a 0.3%-0.7% w / v sodium carbonate solution to degumme them and obtain pure silk fibroin fibers. Dissolve the pure silk fibroin fibers in a lithium bromide solution, stir and dialyze to obtain pure silk fibroin protein. Modify the pure silk fibroin protein by amination, dialyze and freeze dry to obtain amination-modified silk fibroin protein.

[0050] This step begins with boiling silkworm cocoons at high temperature using 0.3%-0.7% w / v sodium carbonate to precisely remove sericin impurities from the cocoon surface. This mild alkaline solution completely degummes the silk fibroin without damaging its polypeptide molecular structure, preserving the protein's original biocompatibility. After degumming, the pure silk fibroin fibers are dissolved in a lithium bromide solution to break down the crystalline structure of the silk fibroin, yielding a soluble silk fibroin stock solution. Lithium bromide ions are then thoroughly removed by dialysis to prevent interference with subsequent cross-linking reactions. Finally, the silk fibroin undergoes amination modification, linking active amino groups into the protein molecules. Subsequent dialysis and freeze-drying purification yields amination-modified silk fibroin capable of participating in Schiff base reactions, providing amino reaction sites for dual-network cross-linking and ensuring effective gel cross-linking.

[0051] S3. N-Isopropylacrylamide and acrylic acid are dissolved in deionized water at a molar ratio of (80-90):(10-20), with a total monomer concentration of 8%-12% w / v. Ammonium persulfate is added as an initiator, and the reaction is carried out under nitrogen protection for 5-7 hours. The product is purified by dialysis and then freeze-dried to obtain poly(N-isopropylacrylamide-co-acrylic acid).

[0052] This step involves blending N-isopropylacrylamide and acrylic acid monomers in a molar ratio of (80-90):(10-20) to regulate the acrylic acid content and balance the gel's temperature-sensitive and pH-responsive properties. The total monomer concentration is controlled at 8%-12% w / v to avoid problems such as excessive viscosity and intense exothermic polymerization due to high concentration, and insufficient polymerization conversion due to low concentration. Ammonium persulfate is used as a water-soluble free radical initiator, and nitrogen protection is applied throughout the process to isolate oxygen and eliminate its inhibitory effect on free radical polymerization, ensuring stable polymerization. A reaction time of 5-7 hours ensures complete monomer polymerization and yields copolymers with the target molecular weight. After the reaction, unreacted monomers and small molecule oligomers are removed by dialysis, and the product is freeze-dried to obtain pure copolymer powder, ensuring that no impurities interfere with the gel phase transition behavior during subsequent blending.

[0053] S4. Aldehyaluronic acid, amino-modified silk fibroin, and poly(N-isopropylacrylamide-co-acrylic acid) are dissolved in phosphate buffer solution with a pH of 7.2-7.6 and mixed at a volume ratio of 1:(0.8-1.2):(0.3-0.7) to obtain an injectable silk fibroin sustained-release gel.

[0054] This step uses a phosphate buffer solution with a pH of 7.2-7.6 to dissolve three polymer raw materials. This pH range closely matches the physiological fluid environment of the human body, ensuring a stable Schiff base crosslinking reaction rate between aldehydes and amino groups and avoiding excessively fast or slow crosslinking caused by abnormal acid-base environments. The three polymer solutions are mixed strictly according to a volume ratio of 1:(0.8-1.2):(0.3-0.7) to precisely match the optimal ratio in the product claims, achieving a sequential reaction of chemical Schiff base crosslinking and temperature-induced physical phase transition. At room temperature, chemical crosslinking first occurs to initially form a network. Upon entering the human body at 37°C, the temperature-sensitive copolymer undergoes a phase transition, constructing a dense interpenetrating network, ultimately yielding an injectable silk fibroin sustained-release gel with dual-response properties. This compounding condition is optimally matched to the in vivo application environment.

[0055] In other embodiments, the molar ratio of sodium periodate to hyaluronic acid glucose unit is 0.25-0.35:1; ethylene glycol diglycidyl ether is used to aminate pure silk fibroin, and the molar ratio of ethylene glycol diglycidyl ether to pure silk fibroin is (1.5-2.5):1; the amount of ammonium persulfate added is 0.5%-1.5% of the total weight of monomers.

[0056] This embodiment, based on the above preparation method, supplements precise molar and mass ratio process parameters to solve the problem of incomplete reactions in the basic process: 1. The molar ratio of sodium periodate to hyaluronic acid glucose units is 0.25-0.35:1 to precisely control the oxidation degree of hyaluronic acid and match the oxidation degree index of the above product; 2. The molar ratio of ethylene glycol diglycidyl ether to silk fibroin is 1.5-2.5:1 to precisely regulate the degree of amino substitution of silk fibroin and avoid excessive or insufficient substitution; 3. The amount of ammonium persulfate added is 0.5%-1.5% of the total monomer mass to ensure that the copolymerization reaction proceeds fully, while avoiding excessive initiator leading to excessively low molecular weight of polymer. This embodiment, by refining the key reaction ratios, ensures that the synthesized product indicators are stable and meet product requirements.

[0057] In other embodiments, step S4, before obtaining the injectable silk fibroin sustained-release gel, further includes: pre-dissolving the active pharmaceutical ingredient in the corresponding buffer solution and then mixing it with the component solutions.

[0058] This embodiment adds a drug-loaded gel preparation step to the above-described blank gel preparation process. This step includes: pre-dissolving the active pharmaceutical ingredient in phosphate buffer and then mixing it with three polymer solutions. This pre-addition method allows the drug to be uniformly encapsulated within the gel's interpenetrating network. Unlike the method of soaking the gel after it has formed, this method effectively inhibits the initial burst release of the drug, ensuring stable early-stage drug release and matching the overall sustained-release effect of the gel.

[0059] Example 1 like Figure 2 As shown, this embodiment provides a method for preparing a pH-responsive injectable sustained-release gel for local tumor chemotherapy, comprising: 1. Material preparation (1) Preparation of aldehyde-modified hyaluronic acid Hyaluronic acid (molecular weight 150 kDa) was dissolved in deionized water to prepare a 2% w / v solution. Sodium periodate was added for oxidation, with a molar ratio of sodium periodate to hyaluronic acid of 0.3:1. The reaction was carried out at room temperature under light-protected conditions for 24 hours. Ethylene glycol was then added to terminate the reaction. The solution was subsequently dialyzed against deionized water for 3 days (molecular weight cutoff of 3.5 kDa), and freeze-dried to obtain aldehyde-modified hyaluronic acid. The oxidation degree of the aldehyde-modified hyaluronic acid was determined to be 25% by 1H NMR spectroscopy.

[0060] (2) Preparation of aminolated silk fibroin Silkworm cocoons were boiled in a 0.5% w / v sodium carbonate solution for 30 minutes to degummify, and this process was repeated three times to obtain pure silk fibroin fibers. The silk fibroin fibers were dissolved in a 9.3 M lithium bromide solution and stirred at 60°C for 4 hours. After dialyzing, a pure silk fibroin protein solution was obtained. Amino-modification was performed using ethylene glycol diglycidyl ether at a molar ratio of 2:1 to silk fibroin, at a reaction temperature of 45°C for 6 hours. The mixture was then dialyzed and freeze-dried to obtain aminated silk fibroin protein. The degree of amino substitution of the aminated silk fibroin protein was determined to be 30% by potentiometric titration.

[0061] (3) Preparation of poly(N-isopropylacrylamide-co-acrylic acid) N-isopropylacrylamide and acrylic acid were dissolved in deionized water at a molar ratio of 85:15 using a free radical precipitation polymerization method. The total monomer concentration was 10% w / v. Ammonium persulfate was added as an initiator (1% of the total monomer weight). The reaction was carried out at 70°C for 6 hours under nitrogen protection. The product was purified by dialysis and then freeze-dried. The molecular weight of the polymer was determined to be 20 kDa by gel permeation chromatography.

[0062] (4) Preparation of drug-loaded gel Doxorubicin was dissolved in phosphate buffer (pH 7.4) to prepare a 10 mg / mL drug solution. Aldehyaluronic acid was then dissolved in the drug solution to prepare a 3% w / v solution, aminolated silk fibroin was dissolved in the same buffer to prepare an 8% w / v solution, and poly(N-isopropylacrylamide-co-acrylic acid) was dissolved in the buffer to prepare a 4% w / v solution. Finally, the three solutions were rapidly mixed at a volume ratio of 1:1:0.5 under ice bath conditions to obtain an injectable drug-loaded pregel solution.

[0063] 2. Performance Characterization (1) Determination of gelation time The pre-gel solution was injected into phosphate buffer at 37°C, and the gelation time was determined using the inverted tube method. The results showed that the gelation time was 5 ± 1 min, which meets the requirements for clinical application.

[0064] (2) Mechanical performance testing The compressive modulus of the gel was determined using a universal testing machine. The results showed that the compressive modulus of the gel was 120±15 kPa, which is much higher than the mechanical strength of a single-component gel.

[0065] (3) pH-responsive release study The drug-loaded gel was placed in phosphate buffer solutions at pH 7.4 and pH 6.5, respectively, and the drug release at different time points was measured. The results showed that the cumulative drug release rate over 24 hours was 78±5% at pH 6.5, while it was only 32±4% at pH 7.4, indicating that the gel has significant pH responsiveness.

[0066] (4) Cytotoxicity evaluation The MTT assay was used to evaluate the toxicity of the gel to fibroblasts. The results showed that the cell viability in the gel extract culture was greater than 95%, indicating that the gel has good biocompatibility.

[0067] Example 2 This embodiment provides a method for preparing a temperature-responsive injectable sustained-release gel for wound healing, comprising: 1. Material preparation (1) Preparation of aldehyde-modified hyaluronic acid Aldehyaluronic acid was prepared according to the method in Example 1, and the amount of sodium periodate was adjusted to achieve an oxidation degree of 20%.

[0068] (2) Preparation of aminolated silk fibroin Aminated silk fibroin was prepared according to the method in Example 1, and the amount of ethylene glycol diglycidyl ether was adjusted to achieve an amino substitution degree of 25%.

[0069] (3) Preparation of poly(N-isopropylacrylamide-co-acrylic acid) Poly(N-isopropylacrylamide-co-acrylic acid) was prepared according to the method of Example 1, with the molar ratio of N-isopropylacrylamide to acrylic acid adjusted to 90:10.

[0070] 2. Preparation of drug-loaded gel Epidermal growth factor (EGF) and dexamethasone were dissolved separately in phosphate buffer at pH 7.4. Aldehyaluronic acid was dissolved in a dexamethasone-containing buffer to prepare a 2.5% w / v solution (dexamethasone concentration 0.5% w / v). Aminated silk fibroin was dissolved in an epidermal growth factor-containing buffer to prepare a 6% w / v solution (EGF concentration 100 μg / mL). Poly(N-isopropylacrylamide-co-acrylic acid) was dissolved in a buffer to prepare a 3% w / v solution. Finally, the three solutions were mixed at a volume ratio of 1:1:0.5 at 4°C to obtain an injectable drug-loaded pregel solution.

[0071] 3. Performance Characterization (1) The gelation time measurement results showed that the gelation time was 4±0.5 min.

[0072] (2) Mechanical property test: The compressive modulus of the gel is 95±10 kPa.

[0073] (3) Temperature-responsive release study: The drug-loaded gel was placed in phosphate buffer at 33℃, 37℃ and 40℃, and the drug release at different time points was measured. The results showed that at 40℃, the cumulative drug release rate over 24 hours was about 60% higher than that at 37℃, indicating that the gel has significant temperature responsiveness.

[0074] (4) Evaluation of wound healing: A diabetic foot ulcer animal model was used, and the drug-loaded gel was injected into the ulcer site. The results showed that the wound healing rate of the gel-treated group was significantly higher than that of the control group, indicating that the gel has a good effect on promoting wound healing.

[0075] Example 3 To optimize the gel formulation, this example compares the performance of different formulations, and the results are shown in Table 1.

[0076] Table 1: Comparison of gel properties of different formulations

[0077] As shown in Table 1, with the increase of the oxidation degree of aldehyde-modified hyaluronic acid, the amino substitution degree of amino-modified silk fibroin, and the content of poly(N-isopropylacrylamide-co-acrylic acid), the gelation time gradually shortens, while the compressive modulus and pH responsiveness gradually increase. Among them, formulation 3 has the best overall performance, but its shorter gelation time may affect the operating time; formulation 2 achieves a better balance between gelation time, mechanical strength, and responsiveness.

[0078] The above are merely preferred embodiments of this application and do not limit the patent scope of this application. Any equivalent structural or procedural transformations made using the content of this application's specification and drawings, or direct or indirect applications in other related technical fields, are similarly included within the patent protection scope of this application.

Claims

1. An injectable silk fibroin sustained-release gel, characterized in that, It consists of the following components: Aldehyaluronic acid with an oxidation degree of 15%-30% and a molecular weight of 100kDa-300kDa; Aminated silk fibroin, with an amino substitution degree of 20%-40% and a concentration of 4%-12% w / v; Poly(N-isopropylacrylamide-co-acrylic acid), with an acrylic acid molar fraction of 5%-20%, a molecular weight of 10kDa-30kDa, and a concentration of 2%-6% w / v; The volume ratio of the aldehyde-modified hyaluronic acid, amino-modified silk fibroin, and poly(N-isopropylacrylamide-co-acrylic acid) is 1:(0.8-1.2):(0.3-0.7). The injectable silk fibroin sustained-release gel forms an interpenetrating network structure through sequential self-assembly of Schiff base reaction and thermosensitive phase transition, exhibiting dual pH / temperature response characteristics.

2. The injectable silk fibroin sustained-release gel according to claim 1, characterized in that, The aldehyde-modified hyaluronic acid has an oxidation degree of 20%-25% and a molecular weight of 150kDa-200kDa; The amino-substituted silk fibroin has an amino substitution degree of 25%-35% and a concentration of 6%-10% w / v; The poly(N-isopropylacrylamide-co-acrylic acid) has an acrylic acid molar fraction of 10%-15%, a molecular weight of 15kDa-25kDa, and a concentration of 3%-5% w / v.

3. The injectable silk fibroin sustained-release gel according to claim 1, characterized in that, The gelation time of the injectable silk fibroin sustained-release gel is 3 min-8 min, and the compression modulus is 50 kPa-150 kPa.

4. The injectable silk fibroin sustained-release gel according to claim 1, characterized in that, It also contains a pharmaceutically active ingredient, which is selected from one or more of chemotherapy drugs, protein drugs, growth factors or anti-inflammatory drugs.

5. The injectable silk fibroin sustained-release gel according to claim 4, characterized in that, The chemotherapy drug is doxorubicin, and the drug loading is 1%-3% of the total weight of the gel; The protein drug is epidermal growth factor, with a loading of 50 μg / mL-200 μg / mL; The anti-inflammatory drug is dexamethasone, with a loading of 0.3%-0.8% w / v.

6. The injectable silk fibroin sustained-release gel according to any one of claims 1-5, characterized in that, The injectable silk fibroin sustained-release gel exhibits a drug release rate that is 2 to 3 times higher at pH 6.5 than at pH 7.

4.

7. The injectable silk fibroin sustained-release gel according to claim 6, characterized in that, The injectable silk fibroin sustained-release gel exhibits a drug release rate that is more than 50% higher at 40°C compared to 37°C.

8. A method for preparing an injectable silk fibroin sustained-release gel as described in any one of claims 1-7, characterized in that, Includes the following steps: Hyaluronic acid was dissolved in deionized water to prepare a 1%-3% w / v solution. Sodium periodate was added to carry out an oxidation reaction for 20-28 hours. Ethylene glycol was added to terminate the reaction. After dialysis with deionized water and freeze drying, aldehyde-modified hyaluronic acid was obtained. Silkworm cocoons are boiled in a 0.3%-0.7% w / v sodium carbonate solution to degumme them, resulting in pure silk fibroin fibers. The pure silk fibroin fibers are dissolved in a lithium bromide solution, and after stirring and dialysis, pure silk fibroin protein is obtained. The pure silk fibroin protein is then aminated, dialyzed, and freeze-dried to obtain aminated silk fibroin protein. N-Isopropylacrylamide and acrylic acid were dissolved in deionized water at a molar ratio of (80-90):(10-20), with a total monomer concentration of 8%-12% w / v. Ammonium persulfate was added as an initiator, and the reaction was carried out under nitrogen protection for 5-7 hours. The product was purified by dialysis and then freeze-dried to obtain poly(N-isopropylacrylamide-co-acrylic acid). The aldehyde-modified hyaluronic acid, the amino-modified silk fibroin, and the poly(N-isopropylacrylamide-co-acrylic acid) were dissolved in phosphate buffer solution with a pH of 7.2-7.6 and mixed at a volume ratio of 1:(0.8-1.2):(0.3-0.7) to obtain the injectable silk fibroin sustained-release gel.

9. The preparation method according to claim 8, characterized in that, The molar ratio of sodium periodate to hyaluronic acid glucose unit is 0.25-0.35:1; The pure silk fibroin was modified by amination with ethylene glycol diglycidyl ether, wherein the molar ratio of ethylene glycol diglycidyl ether to the pure silk fibroin was (1.5-2.5):

1. The amount of ammonium persulfate added is 0.5%-1.5% of the total weight of the monomers.

10. The preparation method according to claim 8, characterized in that, Before obtaining the injectable silk fibroin sustained-release gel, the process further includes: pre-dissolving the active pharmaceutical ingredient in the corresponding buffer solution, and then mixing it with the solutions of each component.